ANALISIS STRTAEGI PEMENUHAN KEBUTUHAN EKONOMI KELUARGA MELALUI USAHA MIKRO DILIHAT DARI PERSPEKTIF EKONOMI ISLAM (Studi Kasus : Kelompok Produksi Ikan Asap Kecamatan Tanjung Raya Kabupaten Agam - Hani, Rahma Almira; Dewi, Sandra (Jurnal Ekonomi Sakti, 2024)
A qualitative approach is used in this type of research. Primary data is gathered from respondents through various means such as documentation, observation, and interviews. Data reduction, data display, and conclusion drafting are the methods utilized in data analysis. From an Islamic economic vantage point, this study seeks to ascertain the methods by which microbusinesses have met economic demands. Utilizing quality raw materials, pricing according to the amount of raw materials available, distributing smoked fish only in local markets, and utilizing social media as promotional media are some of the strategies carried out by the community in Tanjung Raya District, according to this research's results. Beyond that, entrepreneurs can't build successful firms without first acquiring instruction in the ins and outs of microbusiness management. From an Islamic point of view, the smoked fish microbusiness's approach is consistent with sharia law, which governs the procurement of halal substances and other raw materials and the conduct of enterprise. Keyword: Strategy ; Economic Needs; Sharia Micro Enterprises